The revised versions of Kurt Atterberg’s symphonies: Democratic education towards music as a language of us all - Finkel, Carola (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2015)
Kurt Atterberg made subsequent changes to six of his nine symphonies ranging from small retouches to fundamental modifications. The focus of the article is on the Symphonies Nos 4, 5 and 7, which were revised by the composer years after they were published. Since these revisions seem to be still relatively unknown, performances and recordings often utilise out-dated material. The article reconstructs the history of these works and shows the main differences between the original and the revised versions. Surprisingly there are also different performing options concerning the fourth and the seventh symphony.